Pengaruh Peran Public Relations terhadap Brand Image pada Kopi Janji Jiwa - Mita Nur Aisyiyah; Susi Dhewi (UNISBA Press, 2023)
Abstract. The role of Public Relations plays an important role in dealing with problems, especially the company's brand image. This study discusses the role of Public Relations on Brand Image, aiming to analyze the effect of the role of Public Relations on Brand Image on coffee pledges of the soul (a case study at Golden Truly Mall). The sample used in this study was 100 respondents to the promise of soul coffee consumers at Golden Truly Mall. The research method uses a quantitative approach and the sampling technique used in this study is convenience sampling. Data collection was used with non-probability sampling by distributing questionnaires to consumers of coffee-promise souls at Golden Truly Mall. The data collection technique is through the Google form with a scale measurement level such as 5 points and the data confirmation test technique usses the Validity Test and Reliability Test. While the data analysis technique uses the Simple Linear Analysis Technique with the help of IBM SPSS V.21 software with the research results. The output of the regression 2 coefficient value is obtained if the Role of Public Relations has a significant and positive effect on Brand Image on coffee pledges of the soul (Case study in golden truly mall ) because the acquisition of the t test results shows the value of Sig. 0.000 and lower than 0.05 with a t count value of 11.875 which is greater than the table of 1.984 so that Ha is accepted and H0 is rejected with a constant value (a) of 7.126 if these two variables do not experience positive or negative changes. In addition, the regression coefficient value of 0.610 (b) indicates that if there is a positive influence on the role of public relations outside of the current research, then it will also indirectly affect the brand image of kopi promised Jiwa (a case study at golden truly mall) of 0.610. Theseresults were also confirmed by the Coefficient of Determination test, which obtained an R square value of 0.59, meaning that the role of public relations had a significant and positive effect on the brand image of coffee pledges of the soul (a case study at the golden really mall) of 59%. Abstrak. Peran Public Relations memegang peranan penting dalam menghadapi permasalahan khususnya brand image perusahaan. Penelitian ini membahas tentang Peran Humas terhadap Brand Image, bertujuan untuk menganalisis pengaruh Peran Humas terhadap Brand Image terhadap janji jiwa kopi (studi kasus di Golden Truly Mall). Sampel yang digunakan dalam penelitian ini adalah 100 responden janji konsumen kopi soul di Golden Truly Mall. Metode penelitian menggunakan pendekatan kuantitatif dan teknik pengambilan sampel yang digunakan dalam penelitian ini adalah convenience sampling. Pengumpulan data digunakan dengan non-probability sampling dengan menyebarkan kuesioner kepada konsumen coffee-promise souls di Golden Truly Mall. Teknik pengumpulan data melalui Google form dengan skala pengukuran tingkat 5 poin dan teknik uji konfirmasi data menggunakan Uji Validitas dan Uji Reliabilitas. Sedangkan teknik analisis data menggunakan Teknik Analisis Linear Sederhana dengan bantuan software IBM SPSS V.21 dengan hasil penelitian. Keluaran nilai koefisien regresi 2 diperoleh jika Peran Humas berpengaruh signifikan dan positif terhadap Brand Image pada kopi ikrar jiwa (Studi kasus di golden really mall) karena perolehan hasil uji t menunjukkan nilai dari Sig. 0,000 dan lebih kecil dari 0,05 dengan nilai t hitung 11,875 yang lebih besar dari tabel 1,984 sehingga Ha diterima dan H0 ditolak dengan nilai konstanta (a) sebesar 7,126 jika kedua variabel tersebut tidak mengalami perubahan positif atau negatif. Selain itu, nilai koefisien regresi sebesar 0,610 (b) menunjukkan bahwa jika terdapat pengaruh positif peran humas di luar penelitian saat ini, maka secara tidak langsung juga akan mempengaruhi brand image kopi janji Jiwa (studi kasus di golden really mall) sebesar 0,610. Hasil tersebut juga diperkuat dengan uji Koefisien Determinasi yang diperoleh nilai R square sebesar 0,59 artinya peran kehumasan berpengaruh signifikan dan positif terhadap brand image kopi janji jiwa (studi kasus di Golden benar-benar mal) sebesar 59%.